Harassment di Lingkungan Kerja dalam Drama Eiji Harasumento Karya Uchidate Makiko - Sri Wahyuni, Kadek; Yuliani Giri, Ni Luh Kade (Humanis; Vol 22 No 3 (2018), 2018)
The tittle of this research is “Workplace Harassment in Eiji Harasumento drama by Makiko Uchidate”. The purpose of this research is to know the forms of harassment in the workplace which is reflected in Eiji Harasumento drama and also to know the character's efforts in the face of the harassment. The collected data was then analyzed using descriptive analysis method. There are three theories used which are the Theory of Sociology Literature of Wiyatmi (2013), Harassment Theory of Beran & Li (2002) and Semiotics Theory of Danesi (2004). The results of the data analysis shows that in the Eiji Harasumento drama there is a repeated form of harassment but it is done by different characters. 70% harassment is a direct harassment whereas 30% is indirect harassment. Verbal direct harassment is found in 85% from all of direct harassment. While a partly data show is nonverbal direct harassment. Mostly direct harassment is doing by superiors and colleagues on female characters, but there are also data showing harassment by subordinates to superiors in the Eiji Harasumento drama. While overall of indirect harassment doing by fellow woman either by superiors or women of the same position.Then the character's efforts in dealing with abuse are mostly shown by the female characters either directly or indirectly efforts.